Chemotherapy-Induced Cardiotoxicity: Pathophysiology and Prevention - Csapo, Melinda; Lazar, Liviu (Medicine and Pharmacy Reports, 2014)
Along with the remarkable progress registered in oncological treatment that led to increased survival of cancer patients, treatment-related comorbidities have also become an issue for these long-term survivors. Of particular interest is the development of cardiotoxic events, which, even when asymptomatic, not only have a negative impact on the patient`s cardiac prognosis, but also considerably restrict therapeutic opportunities. The pathophysiology of cytostatic-induced cardiotoxicity implies a series of complex and intricate mechanisms, whose understanding enables the development of preventive and therapeutic strategies. Securing cardiac function is an ongoing challenge for the pharmaceutical industry and the physicians who have to deal currently with these adverse reactions. This review focuses on the main mechanism of cardiac toxicity induced by anticancer drugs and especially on the current strategies applied for preventing and minimizing the cardiac side effects.